Chemical Clarification of Sugarcane Juice Using Response Surface Methodology - Prasad, K.; Sharma, H.K. (Asian Journal of Chemistry, 2010)
The potential of chemical clarification of sugarcane juice was assessed using Response Surface Methodology (RSM). The proportions of gelatin, tannin and citric acid were estimated by Central Composite Rotatable Design (CCRD) for the adequacy of clarifica. tion characteristics which were measured in terms of colour and turbidity of sugarcane juice. Minimum turbidity was observed from the addition of 12.20 mg per cent gelatin, 8.48 mg per cent tannin and 0.58 g per cent citric acid. After regressing and analyzing, the optimum proportion for maximum reduction of color and turbidity was observed as 12.26 mg per cent gelatin. 9.10 mg per cent tannin and 0.59 g per cent citric acid respectively.